2018
DOI: 10.1136/bcr-2018-226636
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow metastases in salivary duct carcinoma of the parotid gland

Abstract: Salivary duct carcinoma (SDC) is a rare and extremely aggressive salivary gland cancer. An 81-year-old woman with SDC underwent a total parotidectomy with facial nerve sacrifice and a neck dissection. Following surgery, she was diagnosed with disseminated bone marrow metastases. She underwent chemotherapy and trastuzumab for palliation. We present a case of SDC of the parotid which was diagnosed with disseminated bone marrow metastasis following surgery for the primary. This case also highlights the importance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…[ 3 , 4 ] Studies have reported metastasis to the bone marrow, breast, stomach, and gingiva. [ 9 12 ] However, there are no reports on the metastasis of SDC to the adrenal gland.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 , 4 ] Studies have reported metastasis to the bone marrow, breast, stomach, and gingiva. [ 9 12 ] However, there are no reports on the metastasis of SDC to the adrenal gland.…”
Section: Discussionmentioning
confidence: 99%
“…The medical literature presents the case of a 53-year-old man with a medical history of parotid gland adenocarcinoma, treated with chemotherapy and radiation who came to present a metastatic adenocarcinoma lesion on the left side of the L4 vertebral body [4]. Likewise, another report cites the case of an 81-year-old woman with parotid gland cancer who underwent a total parotidectomy with facial nerve sacrifice and neck dissection, which, after surgery, was diagnosed with widespread metastases in the spinal cord bone [7]. Another study reports the story of a 70-year-old woman who underwent a total excision of the left parotid gland, cervical lymph node dissection and postoperative radiotherapy who, even so, died due to distant metastases 13 months after surgery [8].…”
Section: Discussionmentioning
confidence: 99%